2015
DOI: 10.1042/bj20141063
|View full text |Cite
|
Sign up to set email alerts
|

A stable RNA G-quadruplex within the 5′-UTR of Arabidopsis thaliana ATR mRNA inhibits translation

Abstract: Guanine quadruplex structures (GQSs) play important roles in the regulation of gene expression and cellular processes. Recent studies provide strong evidence for the formation and function of DNA and RNA GQSs in human cells. However, whether GQSs form and are functional in plants remains essentially unexplored. On the basis of circular dichroism (CD)-detected titration, UV-detected melting, in-line probing (ILP) and reporter gene assay studies, we report the first example of a plant RNA GQS that inhibits trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 87 publications
2
46
0
Order By: Relevance
“…For example, a combination of biophysical and biochemical assays was carried out to confirm G4 structure formation by a GQFS located in 5′ UTR of ATR mRNA in A. thaliana (Kwok et al, 2015). The ATR gene encodes a protein kinase, which is activated upon DNA damage and required for the ensuing DNA damage response of the cell including repair, cell cycle arrest and telomere maintenance.…”
Section: G Quadruplex Distribution and Their Genomic Position: Functimentioning
confidence: 99%
“…For example, a combination of biophysical and biochemical assays was carried out to confirm G4 structure formation by a GQFS located in 5′ UTR of ATR mRNA in A. thaliana (Kwok et al, 2015). The ATR gene encodes a protein kinase, which is activated upon DNA damage and required for the ensuing DNA damage response of the cell including repair, cell cycle arrest and telomere maintenance.…”
Section: G Quadruplex Distribution and Their Genomic Position: Functimentioning
confidence: 99%
“…[26] Thea ddition of the complementary sequence (nt 184-208) yielded aT mo f7 3 8 8 Cf or the duplex. [26] Combined with our RTS-HBLMPCR result here (Figure 5A), it is likely that the G4s and P1 helix coexists in full length hTERC,with G4s being more stable than the P1 helix (weak GU pairs and internal loop) under physiological conditions which have high [K + ], about 150 mm.W ec annot rule out the possibility that both structures could form simultaneously with aq uadruplex comprising aCbulge (nt [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. [24] Recent protein binding and RNAmutational studies have suggested that the RNAG4-specific helicase DHX36 is involved in the binding and unwinding of aputative RNAG4 located near the 5 end of hTERC, [27] and that the G4 may facilitate the accumulation of mature hTERC needed for telomere maintenance.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Thes ynthetic or in vitro transcribed (IVT) RNAc an be subjected to in-line probing to detect the presence of RNA G4s. [8] Compared to the abundant rRNAs and tRNAs,m ost cellular transcripts are of lower abundance,t herefore it is challenging to adapt existing approaches to probe the formation and location of G4s in full-length cellular RNAs. Herein, we show that RNAG 4-mediated reverse transcriptase stalling (RTS) can be rationally controlled in ac ation-and G4 ligand-dependent fashion (Figure 1).…”
mentioning
confidence: 99%
“…This probing technique monitors the susceptibility of nucleotides in a structured RNA for hydrolysis (so called in-line cleavage) due to long term incubation under alkaline conditions (36 h at pH 8.3). 34 It is applied on GQs to identify increased cleavage in loop regions in presence of K C compared to Li C and represents a valuable complement to RNase protection. ILP was conducted on AIR-3, to include positions G1 and G19 and also to probe the GQ in its original flanking sequences.…”
Section: -4kmentioning
confidence: 99%
“…For in-line probing 34 (ILP) 5 0 -end labeled RNA (< 1 nM) in 5 mL of nuclease free water was heated to 95 C for 1 min and allowed to refold by cooling to room temperature for 5 min. 0 -end labeled RNA (1 pmol) in 10 mM Tris-HCl (pH 7.5) and 0.5 mM EDTA, heated to 95 C for 1 min and cooled to room temperature for 10 min.…”
Section: Ilp and Rnase T1 Protection Assaysmentioning
confidence: 99%